The Internationalization of US Writing Programs - Weiser, Irwin; Rose, Shirley K. (Book collections on Project MUSE., 2018)
"Multiple theoretical approaches to the work of writing programs and WPAs play in defining goals, curriculum, placement, assessment, faculty and teacher development for international student populations"--Provided by publisher